α-Conotoxin TxIB Inhibits Development of Morphine-Induced Conditioned Place Preference in Mice via Blocking α6β2* Nicotinic Acetylcholine Receptors - Li, Xiaodan; Xiong, Jian; Zhang, Baojian; Zhangsun, Dongting; Luo, Sulan (Frontiers in Pharmacology, 2021)
Morphine, the main component of opium, is a commonly used analgesic in clinical practice, but its abuse potential limits its clinical application. Nicotinic acetylcholine receptors (nAChRs) in the mesolimbic circuitry play an important role in the rewarding effects of abused drugs. Previous studies showed that α6β2* (* designated other subunits) nAChRs are mainly distributed in dopaminergic neurons in the midbrain area, which regulate release of dopamine. So α6β2* nAChRs are regarded as a new target to treat drug abuse. α-Conotoxin TxIB was discovered in our lab, which is the most selective ligand to inhibit α6β2* nAChRs only. Antagonists of α6β2* nAChRs decreased nicotine, cocaine and ethanol rewarding effects previously. However their role in morphine addiction has not been reported so far. Thus, it is worth to evaluate the effect of α-conotoxin TxIB on the morphine induced conditioned place preference (CPP) and its behavioral changes in mice. Our results showed that TxIB inhibited expression and acquisition of morphine induced CPP and did not produce a rewarding effect by itself. Moreover, repeated injection of TxIB have no effect on learning, memory, locomotor activity and anxiety-like behavior. Therefore blocking α6/α3β2β3 nAChRs inhibits the development of morphine induced CPP. α-Conotoxin TxIB may be a potentially useful compound to mitigate the acquisition and/or retention of drug-context associations.